Optimizing Employee Performance: The Role of Competence, Motivation, Knowledge, Work Environment, and Technology Utilization - Tubastuvi, Naelati; Gunawan Putri, Nadya Loverina; Santoso, Suryo Budi; Wahyuni, Sri (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to see the occurrence of updates due to environmental uncertainty post-pandemic on the affected of variables Competence, Motivation, Knowledge, Work Environment and Utilization of Information Technology on Employee Performance. A total of 844 Brebes, Central Java Indonesia Regional Hospital employees were the population in this study. The sample size of 271 people was determined using the Slovin formula. Data was taken in the form of questionnaire results obtained from respondents through questionnaires (google form and paper) The data was gathered using a Likert scale and then analyzed using SPSS software. The findings indicated that Competence, Motivation, Knowledge, Work Environment, and Utilization of Information Technology had a favorable and huge impact on Employee Performance. Competence, Motivation, Knowledge, Work Environment, and Utilization of Information Technology partially demonstrated a noteworthy positive influence on Employee Performance. The outcomes of the research contribute to the knowledge about the application of information technology to enhance staff performance. Information technology provides benefits to employee performance and has a positive influence on employees to improve their performance so as to produce better quantity and quality in improving services.